Data Transmission Performance on IoT Based Monitoring System of Soil Acidity and Moisture Levels in Chili Plantation - Widjaja, Damar; Sujiwa, Theodorus Dendi (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2026)
IoT technology is a development of automation technology that is very helpful in agriculture in maintaining plant health efficiently. It helps farmer in crop monitoring, livestock tracking, weather monitoring, automated irrigation, precision steering, greenhouse automation, and field mapping, remotely via Internet connection. This study will evaluate data transmission performance of IoT technology that is applied in agricultural, especially in chili plantation. The result of this study is that data error performance is acceptable as more than 98% data can be received with no error and the delay performance is more than 2,5 seconds and need to be improved.